1996
DOI: 10.1182/blood.v88.8.3028.bloodjournal8883028
|View full text |Cite
|
Sign up to set email alerts
|

Human blood basophils produce interleukin-13 in response to IgE- receptor-dependent and -independent activation

Abstract: Interleukin-13 (IL-13) is a recently discovered immunoregulatory cytokine. The cellular sources of IL-13 and the regulation of its expression are largely unknown. Here we show that human basophils produce IL-13 in response to IgE-receptor (IgER) crosslinking, IL-3, IL-3 plus C5a, but not C5a alone. Human basophils express IL-13 in a restricted manner since, apart from IL-4, no other cytokines encoded on the cytokine gene cluster (IL-3, IL-5, and granulocyte macrophage-colony-stimulating factor [GM-CSF]), are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 44 publications
4
77
1
Order By: Relevance
“…However, activated basophils [22] and mast cells [23] have also been shown to produce IL-4 and IL-13, and therefore it could be argued that basophils contribute to the cytokine production via allergen-induced cross-linking of Fcepsilon receptors (ER). Because most IL-13 induced by Ig-ER cross-linking in basophils is produced within 4 h [23,37] it is likely that in our experimental set-up with a 4-h pre-incubation before adding the cells to the nitrocellulose plates the IL-13 is T-cell derived. However, IL-3-and IL-3 þ C5a-induced IL-13 production by basophils occurs later.…”
Section: Discussionmentioning
confidence: 99%
“…However, activated basophils [22] and mast cells [23] have also been shown to produce IL-4 and IL-13, and therefore it could be argued that basophils contribute to the cytokine production via allergen-induced cross-linking of Fcepsilon receptors (ER). Because most IL-13 induced by Ig-ER cross-linking in basophils is produced within 4 h [23,37] it is likely that in our experimental set-up with a 4-h pre-incubation before adding the cells to the nitrocellulose plates the IL-13 is T-cell derived. However, IL-3-and IL-3 þ C5a-induced IL-13 production by basophils occurs later.…”
Section: Discussionmentioning
confidence: 99%
“…206,207 The secretion of IL-13 from basophils peaks after approximately 20 hours as opposed to the rapid production of IL-4. 54,99,[208][209][210][211][212][213] Clinical trials are currently in progress to test the efficacy of a mAb neutralizing IL-4 and IL-13 (eg, dupilumab) in severe asthma. 214 Human basophils produce IL-3 71 and IL-31 213 following IgE-dependent activation.…”
Section: Cytokinesmentioning
confidence: 99%
“…The rapid and robust IL-4 production by activated basophils 54,99,204,205,[208][209][210][211][212][213] led to the hypothesis that these cells provide the initial burst of IL-4 used by naïve CD4 + T cells in their differentiation to the Th2 phenotype. 270 CD4 + T cells stimulated in vitro in the presence of basophils differentiate into IL-4-producing Th2 cells even in the absence of exogenous IL-4.…”
Section: Basophil and Mast Cells As Antigen-presenting Cells: An Unmentioning
confidence: 99%
“…Pro-inflammatory cytokines, such as interleukin-4 (IL-4), that are produced by infiltrating Th2 type lymphocytes are felt to play an important role in the pathogenesis of allergic inflammation [1,2]. Recently, we and others have demonstrated that basophils, which similarly infiltrate allergic lesions, also make cytokines, including IL-4 [3][4][5][6], IL-13 [7][8][9], and macrophage inhibitory protein 1␣ (MIP-1␣) [10]. Of specific interest is the fact that basophils generate high levels of IL-4 protein in a matter of a few hours, fitting with the time course of the late-phase reaction to antigen.…”
Section: Introductionmentioning
confidence: 99%